Reverse vaccinology for hookworms: a rational selection of vaccinable antigens against parasitic nematodes - Sotillo Javier; Quinzo Mónica; García Juan José; Martín-Galiano Antonio J. (Parasite)
Reverse vaccinology is a time- and cost-effective approach to identify potential vaccinable antigens for further in vivo experimental validation. Despite its wide application to multiple organisms, the use of in silico vaccine development tools to parasitic nematodes has been limited. Herein, we have used the rodent hookworm Nippostrongylus brasiliensis as a mouse model for the human hookworm Necator americanus to identify potential vaccine candidates against the latter. Our strategy combined advanced bioinformatic evaluations with knowledge-based criteria. A cumulative rating of antigenic properties was performed resulting in a global prioritization scoring for an updated N. brasiliensis proteome of 22,796 proteins assigned. Evaluation criteria included homology to the human counterpart N. americanus, absence of mammalian homologs, cellular location by computational predictors, as well as mass spectrometry data, proteolytic activity of the evaluated protein within the parasite, presence of conserved domains, predicted humoral epitopes, and MHC class II epitope population coverage. To assign one global score representing these characteristics, cumulative scoring was performed. This analysis provided a group of 56 potential candidates, including 11 proteins associated with parasite survival and establishment. Remarkably, the second highest score was assigned to an aspartic protease homologous of the N. americanus vaccine-candidate Na-APR-1, which supports the relevance of this approach. Allergenicity and toxicity of the selected molecules were also predicted to anticipate side effects of future candidates. This comprehensive approach provides valuable insights for the rational design of new vaccines against N. americanus, the results of which, however, must be validated in vivo.